Ethanol Extract of Black Cumin Seed (Nigella Sativa) Reduces Expression Kidney iNOS in Mice Model Preeclampsia - Rubiati Hipni (Medical Laboratory Technology Journal, 2019)
This study aims to analyze the effect of ethanol extract of black cumin seeds (Nigella Sativa) on iNOS expression in the kidney of mice model preeclampsia. Design This study uses an experimental design with a posttest only control group design. Using a mice model preeclampsia. This study was divided into 6 groups: negative control, positive control (preeclampsia model), model + black cumin seed extract 500 mg/KgBB/day, 1000 mg/KgBB/day, 1500 mg/KgBB/day, and 2000 mg/KgBB/day days, after surgery on mice then examined iNOS Kidney expression by methods Immunohistochemical. Data from observations were analyzed by one way ANOVA test. The result there is an effect of ethanol extract of black cumin seeds on renal iNOS expression in mice model preeclampsia (p